THE MANAGEMENT OF THE MEDAN AKSARA ORPHAN FRIENDS DORMITORY IN IMPLEMENTING ISLAMIYAH VALUES AND FORMING A GENERATION OF AKHLAKUL KARIMAH - Dinda; Simamora, Irma Yusriani (Al-Mubin, 2025)
The application of Islamic values in dormitory management plays an important role in forming a generation with good morals. This research aims to explore how the dormitory management applies Islamic values in forming a generation with good morals. In addition, this study also analyzes the parenting system applied and its effectiveness in shaping the character of foster children. Using a qualitative method through interviews with the head of the dormitory, this study examines the role of caregivers, the dormitory environment, and the educational programs applied. The results of the study show that an approach based on Islamic education, discipline habituation, and a reward and punishment system play an important role in building children's character. In addition, the presence of competent caregivers and appropriate coaching methods are key factors in the success of the boarding program. This study provides insight into the importance of a holistic approach in the care of orphans to support their development optimally